2008
DOI: 10.1159/000136900
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features of Symptomatic Carotid Plaques in Patients with Impaired Glucose Tolerance and Diabetes (Oxford Plaque Study)

Abstract: Background: Diabetes is associated with an increased risk of incident stroke and both early and late recurrent stroke after transient ischaemic attack. Some small studies have suggested that atherosclerotic plaques from diabetics have a higher prevalence of unstable features than plaques from non-diabetics but results have been inconsistent. Method: We made detailed histological assessments of 526 plaques from consecutive patients undergoing carotid endarterectomy for recently symptomatic stenosis and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 64 publications
2
28
1
1
Order By: Relevance
“…1,13,24 However, these observations could not be confirmed in the more recent Oxford Plaque Study, which showed no difference in inflammatory cells between plaques from subjects with DM II and subjects with normal glucose tolerance. 25 In line with this study, we found no difference in inflammatory markers and macrophage staining between DM II and nondiabetic plaques in the present study. It is possible that these inconsistencies reflect differences in study design, cohorts, or analytic approach.…”
supporting
confidence: 90%
“…1,13,24 However, these observations could not be confirmed in the more recent Oxford Plaque Study, which showed no difference in inflammatory cells between plaques from subjects with DM II and subjects with normal glucose tolerance. 25 In line with this study, we found no difference in inflammatory markers and macrophage staining between DM II and nondiabetic plaques in the present study. It is possible that these inconsistencies reflect differences in study design, cohorts, or analytic approach.…”
supporting
confidence: 90%
“…For this purpose, cerebral angiography, ultrasound, and 3D-CTA have been employed. However, recent studies have clarified that the morphology [30] and/or components of carotid plaque are alternative factors to determine the outcome in patients with carotid artery stenosis [10,11,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, CSE or components of CS were suggested to increase intraplaque inflammation and intraplaque neovascularization. [30][31][32][33] Intraplaque inflammation and intraplaque neovascularization lead to intraplaque hemorrhage and subsequent necrotic core enlargement. 26 Furthermore, CSE was found to cause an increased sympathetic activity leading to a rise in blood pressure, pulse rate, and vasospasm, which might create a high-mechanical stress zone near a vulnerable plaque.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%